Forging bonds beyond the national area. Exploring international interaction among radical right populist parties: the case of AUR - Boldrini, Matteo; Collini, Mattia; Lup, Oana; Soare, Sorina (Frontiers in Political Science, 2025)
The rise of radical right populism across Europe has been linked to broader societal shifts and individual susceptibility to populist narratives. While existing research has explored electoral dynamics, leadership, and organizational strategies, less attention has been given to how these parties gain legitimacy through international engagement. This paper introduces the concept of legitimation from abroad, a multilayered process through which radical right populist parties align with international actors to counter stigmatization and bolster their credibility. Using the Alliance for the Union of Romanians (AUR) as a case study, we analyze how transnational interactions, such as intellectual networking, participation in European political groups and symbolic international events, contribute to their political survival and institutional recognition. Drawing on party documents and secondary literature, this study provides new insights into how radical right populist parties strategically leverage the international arena to enhance their legitimacy and sustain their political influence.